Motivasi dan Tantangan Mahasiswa dalam Berwirausaha: Perspektif Generasi Muda di Era - Pandu Rudy Widyatama; Mohamad Rifqi Hamzah (CV ULIL ALBAB CORP, 2025)
The development of digital technology provides great opportunities for students to be entrepreneurs with smaller capital and wider access to marketing. However, not all students are able to survive in their businesses because they face various challenges, such as limited capital, market competition, and time management between college and business. This research aims to explore the motivations and challenges of students in running a business in the digital era, as well as the strategies they apply to overcome these obstacles. The research method used is qualitative with a case study approach, involving observation, in-depth interviews, and documentation of entrepreneurial students. The results of the study show that students are encouraged to be entrepreneurial because of economic factors, time flexibility, and personal interest in business. Most use Instagram and WhatsApp as the main marketing platforms, but face obstacles in capital management and digital competition. To overcome these challenges, students implement pre-order strategies, collaboration with suppliers and marketplaces, as well as digital marketing and branding. This study recommends support from universities in the form of entrepreneurship training and access to funding, so that students can be better prepared to face digital business competition.